Synthesis of glucose-derived solid acid catalyst for production of biodiesel from palm fatty acid distillate - Ibrahim, Mohd Lokman; Rashid, Umer; Zainal, Zulkarnain; Yap, Taufiq Yun Hin (2014)
A potential catalyst derived from carbohydrate precursor was developed for the production of biodiesel. Carbohydrate-derived solid acid catalyst was synthesized by sulfonating the incomplete carbonized D-glucose (ICG) using concentrated sulfuric acid. Sulfonated catalyst was also used to study its ability to catalyze the esterification of palm fatty acid distillate (PFAD) which consists of more than 85 wt.% free fatty acids (FFA). Sulfonated carbonized D-glucose (ICG-SO3H) catalyst was characterized by determining its acid site density, functional groups, thermal stability, surface area and morphological analysis. The produced ICG-SO3H catalyst illustrated high surface area, 10.67 m2 g-1. Furthermore, investigation on produced catalyst was conducted to determine the effect of pyrolysis and sulfonation time. The catalytic activities of the catalyst were performed using conventional reflux method. The ICG-SO3H demonstrated 96% conversion of FFA to fatty acids methyl esters (FAMEs) within a short time (2 h) at 75 °C of reaction temperature at optimum level of methanol to PFAD molar ratio (10:1) and catalyst loading (2.5 wt.%). It can be deduced from the results that ICG-SO3H catalyst can prove to be a potential catalyst to esterify high FFA feedstocks especially PFAD to produce low cost biodiesel.